Genetic regulation of the ramA locus and its expression in clinical isolates of Klebsiella pneumoniae - Rosenblum, R.; Khan, E.; Gonzalez, G.; Hasan, R.; Schneiders, T. (International journal of antimicrobial agents, 2011)
Tigecycline resistance has been attributed to ramA overexpression and subsequent acrA upregulation. The ramA locus, originally identified in Klebsiella pneumoniae, has homologues in Enterobacter and Salmonella spp. In this study, we identify in silico that the ramR binding site is also present in Citrobacter spp. and that Enterobacter, Citrobacter and Klebsiella spp. share key regulatory elements in the control of the romA–ramA locus. RACE (rapid amplification of cDNA ends) mapping indicated that there are two promoters from which romA–ramA expression can be regulated in K. pneumoniae. Correspondingly, electrophoretic binding studies clearly showed that purified RamA and RamR proteins bind to both of these promoters. Hence, there appear to be two RamR binding sites within the Klebsiella romA–ramA locus. Like MarA, RamA binds the promoter region, implying that it might be subject to autoregulation. We have identified changes within ramR in geographically distinct clinical isolates of K. pneumoniae. Intriguingly, levels of romA and ramA expression were not uniformly affected by changes within the ramR gene, thereby supporting the dual promoter finding. Furthermore, a subset of strains sustained no changes within the ramR gene but which still overexpressed the romA–ramA genes, strongly suggesting that a secondary regulator may control ramA expression.